Reinforcement of variability facilitates learning in humans. Issue 3 (9th October 2018) - Hansson, Jocelyn; Neuringer, Allen
Abstract : Studies with rats and pigeons showed that reinforcement of response variability improved learning of difficult response sequences. The results suggested that concurrent reinforcement of variability might be a helpful tool when educators or therapists attempt to teach individuals with learning difficulties. However, similar experiments with humans failed to confirm the results. In fact, in the human case, concurrent reinforcement of variability interfered with learning. The present experiment studied the same phenomenon with human participants in the context of a computer‐based game. Our results were consistent with the nonhuman animal findings. When students in our experiment were concurrently reinforced for sequence variability, they were more likely than control participants to learn a difficult response sequence. We conclude that reinforcement of variability can facilitate learning—in humans as well as animals —and discuss possible reasons for the difference between our results and the previous human findings.